2000
DOI: 10.1007/s150100050049
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and C-Reactive Protein Levels in Community-Acquired Pneumonia: Correlation with Etiology and Prognosis

Abstract: Our data indicate that in patients admitted to the hospital with CAP, measurement of PCT gives information about the severity of the disease, and may aid the physician to differentiate typical bacterial etiology from atypical etiology, and thereby to choose appropriate initial antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
114
2
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 43 publications
21
114
2
8
Order By: Relevance
“…The present study confirms the findings of previous studies that PCT is a good predictor of pneumonia severity [16,18,19,22]. Patients with a higher CRB-65 score had significantly higher PCT levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confirms the findings of previous studies that PCT is a good predictor of pneumonia severity [16,18,19,22]. Patients with a higher CRB-65 score had significantly higher PCT levels.…”
Section: Discussionsupporting
confidence: 92%
“…High plasma concentrations of PCT are typically seen in sepsis, meningitis and pneumonia [12][13][14][15][16][17]. PCT also seems to be a prognostic factor in sepsis and pneumonia [18,19].…”
mentioning
confidence: 99%
“…While the relationship between PCT and severity or prognosis has been thoroughly investigated in adults during either systemic infections or CAP [15][16], only few authors [17][18][19] have looked into the relationship between PCT values and severity for pediatric infectious diseases. Specifically, in the cases of bacterial infections, such as meningococcal disease and urinary tract infections, or bacterial sepsis, there is an association between high PCT levels and poor prognosis.…”
Section: Pct and Disease Severitymentioning
confidence: 99%
“…[8][9][10][11] The few observational studies of adults conducted in primary care showed that fever, headache, painful cervical lymph nodes, diarrhea and rhinitis predicted bacterial lower respiratory tract infection, but sample sizes in these studies were small. 4,5 Additional testing with the inflammation markers C-reactive protein and procalcitonin is potentially useful in predicting bacterial infection.…”
Section: Resultsmentioning
confidence: 99%